2010
DOI: 10.1007/978-3-642-16552-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Using a Semantic Wiki for Documentation Management in Very Small Projects

Abstract: The emerging ISO/IEC 29110 standard Lifecycle profiles for Very Small Entities is targeted at very small entity (VSE) having up to 25 people, to assist them unlock the potential benefits of using software engineering standards. VSEs may use semantic web technologies to improve documentation management infrastructure and processes. We proposed to use a semantic wiki for documentation management based on an identification scheme inspired from an IFLA proposition called Functional Requirements for Bibliographic R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Literature reports contributions related to the ISO/IEC 29110 25 in several industrial contexts. [26][27][28][29][30] Basically, these contributions are related to its adoption, 31,32 but in general their contributions are wide. 33 In fact, this kind of organisations is facing several hurdles 34 including project management and software implementation perspectives.…”
Section: Very Small Entities and System Life-cycle Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature reports contributions related to the ISO/IEC 29110 25 in several industrial contexts. [26][27][28][29][30] Basically, these contributions are related to its adoption, 31,32 but in general their contributions are wide. 33 In fact, this kind of organisations is facing several hurdles 34 including project management and software implementation perspectives.…”
Section: Very Small Entities and System Life-cycle Processesmentioning
confidence: 99%
“…Literature reports contributions related to the ISO/IEC 29110 in several industrial contexts . Basically, these contributions are related to its adoption, but in general their contributions are wide .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several industrial experiences have been reported applying the ISO/IEC 29110 . Its adoption is controversial, and researchers have provided contributions from several ISO/IEC29110 perspectives .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors are researching on tailored lifecycles for VSEs through the use of composition trees for modelling processes . From a project management perspective, there are contributions focused on documenting management aspects in VSEs context . From a technical perspective, VSEs should overcome new technologies or approaches such as microservices …”
Section: Introductionmentioning
confidence: 99%